2022
DOI: 10.1002/rcs.2477
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal robotic‐assisted thoracoscopic surgery for early‐stage lung cancer with the Da Vinci Xi: Initial experience of two cases

Abstract: Background: Minimally invasive surgery (MIS) techniques, currently considered the gold standard in the treatment of early-stage non-small cell lung cancer (NSCLC), are mainly represented by video-assisted thoracoscopic surgery (VATS), both uniportal and multiportal, and by robotic-assisted thoracoscopic surgery (RATS). While multiportal RATS has been accepted as a valid alternative to VATS, carrying the advantages of three-dimensional high-definition visualisation and improved maneuverability, very few reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A total of 137 studies on the application of u-RATS were identified for inclusion, with 12 progressing to inclusion (5 cohort series, 7 case reports) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The cohort series are presented in Table 3.…”
Section: Study Characteristics and Baseline Demographic Data (See Tab...mentioning
confidence: 99%
“…A total of 137 studies on the application of u-RATS were identified for inclusion, with 12 progressing to inclusion (5 cohort series, 7 case reports) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The cohort series are presented in Table 3.…”
Section: Study Characteristics and Baseline Demographic Data (See Tab...mentioning
confidence: 99%
“…It may be cheaper, less painful, and allow easier management in case of emergency. 11 Apart from the group, that introduced the uniportal robotic approach, there have been very few publications on uniportal RATS, [12][13][14] and it remains uncertain whether this technique and teaching can be replicated and implemented in different settings by different surgeons. The purpose of this paper is to report our first experience with the uniportal robotic approach for anatomic lung resections performed by a single surgeon.…”
mentioning
confidence: 99%